2008
DOI: 10.1177/15910199080140s215
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Percutaneous Vertebroplasty at Cemented Vertebra with Fluid Sign and Recurrent Pain

Abstract: Six patients (three females and three males) were referred from their clinicians for evaluation with complaints of recurrent pain. A follow-up MRI showed fluid at the cemented vertebral bodies. Repeat percutaneous vertebroplasty (PV) was performed in these six patients at the cemented vertebrae. Pain scores, mobility scores, and spine MRIs before the 1st P V, prior to the repeat PV, and 1 and 3 months after the repeat PV were obtained. One month after the repeat P V, the six patients had a mean pain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The current study showed that pre-exiting VCFs increased the occurrence of new VCFs. The patients with a low BMI are at higher risk of subsequent VCFs of the spine is generally accepted 9) . It was postulated that lower BMI may be associated with weaker vertebra, which is subject to the direct effect of adjacent vertebral augmentation.…”
Section: / Ajpmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study showed that pre-exiting VCFs increased the occurrence of new VCFs. The patients with a low BMI are at higher risk of subsequent VCFs of the spine is generally accepted 9) . It was postulated that lower BMI may be associated with weaker vertebra, which is subject to the direct effect of adjacent vertebral augmentation.…”
Section: / Ajpmentioning
confidence: 99%
“…After first report of vertebroplasty procedures by Galibert et al in 1987 6,19) , percutaneous vertebroplasty (PVP) is a well-established technique for treating osteoporotic compression fractures and an efficient procedure to treat pain due to osteoporotic vertebral compression fracture (VCF) 1,3,[5][6][7][9][10][11][12][13][17][18][19][20] . Recent study reported that overall success rates of PVP as 60% to 90% with providing immediate significant pain relief 17) , restoring the patients' quality of life, and shortening the hospitalization days 13) .…”
Section: Introductionmentioning
confidence: 99%